Laparoscopic sigmoid resection for diverticular disease has no advantages over open approach: midterm results of a randomized controlled trial - Raue, Wieland; Paolucci, V.; Asperger, W.; Albrecht, R.; Büchler, Markus W.; Schwenk, W. (Langenbeck's archives of surgery, 2011)
Elective laparoscopic sigmoid resection (LSR) for symptomatic diverticular disease is supposed to have significant short-term advantages compared to open surgery (open sigmoid resection (OSR)). This opinion is rather based on inferences from trials on colonic resections for malignant diseases or minor laparoscopic surgery. This randomized controlled trial was conducted to compare quality of life as well as morbidity and clinical outcome after LSR vs. OSR following a midterm follow-up period.
Gesehen am 12.09.2022